Pengaruh Rasio Solvabilitas, Aktivitas, Likuiditas dan Book Tax Differences terhadap Pertumbuhan Laba - Davin Valerian; Ratnawati Kurnia (Ultima Accounting : Jurnal Ilmu Akuntansi, 2018)
Profit growth was important information for investors and company itself to make the right decisions. The objective of this research is to examine empirical evidence about solvability ratio, activity ratio, liquidity ratio, and book tax differences towards profit growth. The objects in this research are retail and manufacturing companies listed at Indonesian Stock Exchange for the period 2014-2015. The data used in this research was secondary data collected from financial statements at Indonesian Stock Exchange. The samples were selected using purposive sampling method. The data analysis technique used in this research is multiple regression. The results of this research showed that book tax differences proxied by permanent differences has significant effect towards profit growth. Then solvability ratio proxied by debt to total asset and debt to equity ratio have no significant effect towards profit gowth. Activity ratio proxied by inventory turnover, liquidity ratio proxied by current ratio, and book tax differences proxied by temporary differences have no significant effect towards profit growth.Keywords: Activity Ratio, Book Tax Differences, Liquidity Ratio, Profit Growth, Solvability Ratio